HINDU NEW YEAR CELEBRATION AND INDIAN CALENDAR - Kanta; Shankar, Uma (ShodhKosh: Journal of Visual and Performing Arts, 2023)
’Nav Samvatsar Abhinandan’ has special importance in India, the land of festivals. The Shukla Pratipada of Chaitra month is also celebrated as Varsha Pratipada or Yugadi. In fact, all festivals are representative of Indian cultural treasure. These are actually symbols of recollection of historical events, which not only awakens the sense of consciousness towards cultural traditions, but also strengthens the sense of faith, trust and respect towards festivals. Regarding the beginning of Hindu Navsamvatsar or New Year, there is mention of various theories of chronology accepted from Vedic era and many incidents that happened on the scene of Indian history. For example, Pitamah Brahma started the creation from this day, the beginning of the present Kaliyug is also considered to be on this day. This is reflected in many other forms like the beginning of Navaratri, beginning of new Panchang etc.